Beliefs, knowledge and popular health practices in women living in poverty - Juárez, María Paula (Horizonte Sanitario, 2021)
Objective: The article reflects on knowledge, beliefs and practices in health, illness and care of women in poverty in the south of the province of Córdoba, Argentina. It is positioned in the conceptual proposal of the sanitary psychologist Enrique Saforcada on “the fundamental contexts of public health”, focusing on the “context of the lay health concepts and practices of society”. Materials and methods: From a qualitative methodology, stories of 11 women living in three communities living in poverty are recovered. The sample was made up of voluntary informants according to their willingness to participate in the study. Semi-structured interviews were conducted based on the axes of knowledge, practices and beliefs in health. The qualitative analysis was developed, in a synchronic key, building a theoretical explanatory scheme supported by Grounded Theory procedures and, in a diachronic key, interpreting the data from the narrative biographical perspective. Results: The categories emerged: construction and dynamization of popular knowledge in health in the lives of women; uses and customs in healing / healing practices; healing / healing oriented beliefs. Conclusions: The conceptions, practices and beliefs in health-disease-care make up popular knowledge emerging from intersubjective and dialogical processes where the protagonists are adult and young women who, as teachers and learners, dynamize a particular type of social interaction based on meanings of health , disease, care and attention linked to their life experiences, forming an epistemic body that nurtures actions for the promotion and protection of health, as well as care for disease and restoration of health. It reflects on: a) the importance of knowledge in health in the face of scenarios of expropriation / appropriation of health; b) the paradigms underlying these lay conceptions and practices.